Correlation Study on Physico-chemical Parameters on Water Quality of Gaula River, Haldwani, Nainital, Uttarakhand, India - Bisht, Arti; Mehra, Rajni (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2024)
The present study was carried out to determine the variations of physicochemical parameters on the Gaula River Haldwani in Nainital district, Uttarakhand from March 2019 to February 2020. Thirteen parameters were taken in consideration for analysis of the river water such as Temperature, Transparency, Turbidity, Total Dissolved Solids, pH Value, Total Hardness, Free CO2, Dissolved Oxygen, Biological Oxygen Demand, Chemical Oxygen Demand, Phosphate, Nitrate and Nitrite. The observed values of various parameters of water samples were almost under the permissible limit determined by World Health Organization and Bureau of Indian Standards except Turbidity, Biological Oxygen Demand and Nitrite. Correlation Coefficient showed highly significant positive and negative relationship. A large number of factors and geological conditions affect the correlations between various water quality parameters directly or indirectly. The main objective of this study was to assessing the river water quality in three different sites with respect to drinking and irrigation purposes. The correlation values are helpful in calculating the concentration of water quality of the physicochemical parameters of the water sample.